Source of Explant and Light Spectrum Influence in Adventitious Shoot Regeneration of Prunus salicina Lindl. (Japanese plum) - Carmen López-Sierra; José E. Cos-Terrer; Miriam Romero-Muñoz; Margarita Pérez-Jiménez (Plants)
Light influence on shoot regeneration in Prunus salicina is a complex interaction that has been studied for the first time. Japanese plum plants were regenerated from calli and seeds of the scion cultivar ‘Victoria’. The effect of four different light spectra (white, blue, red, and mixed), along with three 6-benzyladenine (BA) concentrations (1, 1.5, and 2 mg L−1), was studied in these two sources of explants. Organogenic calli were derived from the base of stem explants of the scion cultivar ‘Victoria’, whereas cotyledons and embryogenic axis slices were used as seed explants. Calli cultured with 2 mg L−1 of BA and mixed light or 2.5 mg L−1 of BA and control light showed the highest regeneration rates, with no significant differences compared to other treatments. Seed explants exposed to 2.5 mg L−1 of BA and red light exhibited significantly higher organogenesis. In comparison, those in 1.5 mg L−1 of BA with blue light or 2.5 mg L−1 of BA with mixed/control light showed no regeneration. BA concentration did not have a significant effect in the induction of somatic shoots from any explant source. In contrast, a strong interaction between light and BA was noticed. This work presents a protocol that can be applied in transformation and editing research as light spectrum studies continue to advance.